The Impact of Problem-Based Learning on Religious Poetry Writing Skills Among Senior High School Students - Marini Razanah; Nani Solihati; Zamah Sari (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on the religious poetry writing skills of tenth-grade high school students. The study used a quasi-experimental pretest–posttest nonequivalent control group design and was conducted in a public high school in the odd semester. The subjects were 60 tenth-grade students who were divided into two groups: the experimental group (PBL; n=30) and the control group (conventional learning; n=30). The main instrument was a religious poetry writing performance test on the pretest and posttest which was assessed using an analytical rubric on a scale of 1–4. Data were analyzed using descriptive statistics (mean±SD), independent t-test for initial equality, paired t-test for changes in groups, and Cohen’s d (within), Hedges’ g (between), and η² (Group×Time) effect sizes. The results showed that the experimental group experienced significant improvements in all indicators (p<0.05) with moderate to large effects, while the control group showed no significant changes (p>0.05). Thus, PBL is more effective than conventional learning in improving the quality of religious poetry of class X students and is recommended for poetry writing learning in high school.